FEATURES OF MODERN TRANSPORT FORWARDING BUSINESS - Razumova, K. M.; Novalska, N. I.; Klymenko, V. V. (Systems and Technologies, 2023)
The article is devoted to the study of the peculiarities of the transport and forwarding business. It has been investigated that the activities of modern transport and forwarding companies are aimed at comprehensive customer service for the integrated satisfaction of their needs (reducing the risk of loss or damage to the cargo, minimizing the sender’s financial and time costs for transporting the cargo). It was determined that in recent years the development of the transport and forwarding business took place in the conditions of globalization of production and distribution; formation of organizational and legal frameworks for the activities of freight forwarders; integration of transport modes and development of intermodal and multimodal transportation technologies; formation of a modern concept of warehouse service; integration of material flows in the system of international movement of goods. It was substantiated that the organization of the activities of transport forwarders is carried out both in accordance with regulatory and legal acts, and within the framework of self-regulatory organizations that unite professionals of the transport and logistics business, develop standards, norms and rules for the work of forwarders, and defend their interests. It was found that the presence of a wide and developed network of forwarding companies is an integral part of the infrastructure of transport systems. Particular attention is paid to the identification of problems and peculiarities of the activities of transport and forwarding companies in the conditions of full-scale russian aggression. At that time, the Ukrainian transport and forwarding business faced numerous negative factors, including the suspension of air traffic, blocking of sea and river ports, queues at the border, the destruction of the domestic transport infrastructure and the unpreparedness of the infrastructure of Eastern European countries for new formats of work with Ukraine. Currently, processes are taking place in Ukraine that contribute to the restoration of the transport infrastructure, the improvement of the organization of transport forwarding and logistics activities, new logistics routes are being developed and old ones are being restored for the transportation of goods in international traffic, and the border infrastructure is developing.